War Burials as a Method of Instrumentalizing the Memory of World War II - Varian, Oksana (Social consequences of war, 2024)
The practice of Russia’s using burials from World War II to construct an aggressive concept of memory about the war in Soviet and post-Soviet public space and the subsequent use of memory as a tool of military aggression is considered. It was established that Ukraine and Russia formed different types of memories about World War II. Ukraine’s memory of World War II is the happiness of victory combined with the conscious memory of its tragic price, reflected in the phrase “Never again”. Russia’s memory of World War II is different – aggressive, justifying all war crimes with the right of the winner, supported by the militarization of society, personified by the slogans “grandfathers fought” and “we can do it again”. Based on research on military burials from 1941–1944 in the Zaporizhzhya region, three characteristic features of the attitude of the Soviet authorities towards military burials were identified and analyzed using specific examples: depersonalization of the memory of the war; a formal approach to burials; marking central parts of public space in cities and villages with military burials. A typology was carried out and statistical data were presented on the number of burials from the period of World War II in the Zaporizhzhia region. The general situation of the organisation of military burials on the territory of the Zaporizhzhia region is presented on the example of the city of Melitopol – a strategic city in the German-Soviet war of 1941–1945 and the ongoing Russian-Ukrainian war, currently occupied by the Russians. It was determined that Russia used World War II monuments in the occupied territory as a component of ideological propaganda. At the same time, 60% of the cultural heritage monuments of the Zaporizhzhia region destroyed by shelling by Russian troops are military burials from the period of World War II.